Digital marketing training for salted fish SMEs in Pela Tourism Village, Kutai Kartanegara Regency - Heldina Pristanti; Siti Nurhasanah; Raudah Ahmad; Rakhel Lia (Universitas Muhammadiyah Magelang, 2021)
One of the businesses that is currently starting to develop in Pela Village is the salted fish business. However, the income of the Pela Village community is very low. One of the contributing factors is the lack of promotions carried out to promote their products in the market. Based on these problems, this community service aims to train the Pela Village community in marketing salted fish products through digital marketing. The PkM team facilitates computers for people who do not have personal computers. This program is carried out through counseling and workshop methods. The results show that partners have succeeded in creating layouts for their product sales promotions digitally and posted on marketplaces and social media. Through the available promotion media, it is hoped that they can increase the sales.